Financial Performance of The Main Palm Oil Companies in Indonesia and The Influencing Factors - Muhammad Siddik Elfian; Harianto; Nimmi Zulbainarni (School of Business, IPB University (SB-IPB), 2023)
Palm oil is a promising agricultural commodity in Indonesia. Many companies enter this industry. Business development and area expansion done to fulfill the world market needs for oil palm plantation products, especially Crude Palm Oil (CPO). Business development requires capitals. Capitals obtained by oil palm plantation companies from investors and creditors through shares and loans. Investors and creditors need a criteria to invest in this industry. The criteria commonly used is seeing the company's financial performance. The company's financial performance can be analyzed using Economic value added. In this study, there are seven Indonesian oil palm companies that will be analyzed using Economic value added (EVA). EVA is chosen because it can decide the companies’ financial performance properly. There are several factors that affect the value of EVA. These factors are the Rupiah exchange rate, the Indonesian bank interest rate, corporate profits, pandemic dummy and CPO prices. These factors are seen for their influence on the value of EVA by using panel data regression analysis. The factors that affect the value EVA are the rupiah exchange rate and the company's profit. Oil palm companies can maximize the opportunity of those impacted factors to gain profit and fix their financial performance. Keywords: palm oil companies, financial performance, EVA, panel data regression